The utility of forewing geometric morphometrics for species discrimination in the caddisfly genus Xiphocentron (Trichoptera: Xiphocentronidae), with the description of six new species - Vilarino, Albane; Sganga, Julieta V.; Bispo, Pitágoras C. [UNESP] (Elsevier, 2024)
Xiphocentron species are often distinguished only by subtle differences in genital structures, and species are usually described with small type series not allowing the distinction of intra and interspecific variation. Herein we evaluated for the first time the use of the forewing geometric morphometrics to verify Xiphocentron species distinctiveness at a population level. Most of the known specimens from Atlantic rainforest and Brazilian savanna were analyzed, including six new species (Xiphocentron guarani sp. n., Xiphocentron karaja sp. n., Xiphocentron schmidi sp. n., Xiphocentron tapuia sp. n., Xiphocentron tupi sp. n., Xiphocentron xokleng sp. n.). Species were analyzed in two comparative datasets of species with similar genitalia. Forewing shape among species differed statistically. Canonical variate analysis showed partial overlapping of wing shape in most species except to X. karaja sp. n. and X. xokleng sp. n. Cross-validation test was able to discriminate species with an overall correctness of 64.65 % and 73.15 % in each dataset. So, forewing morphometrics showed moderate to high effectiveness depending on the Xiphocentron species, but had a lower informativeness compared to the >80 % correctness shown in studies with another Trichoptera genus, Smicridea. The lower forewing distinction in Xiphocentron might be associated with a stronger functional selection of wing traits related to miniaturization. Additionally, two very similar species described from the same locality Xiphocentron steffeni and Xiphocentron ilionea were re-described, clarifying their distinctiveness.
Keywords: Cryptic species; Geometric morphometrics; Integrative taxonomy